Effects of spreadsheet towards learners’ usage of mathematical language - Kok Fui, C.; Syed Zamri, S.N.A. (2014)
Language has been an essential element in mathematics education as it is a tool used between individuals to convey the information of mathematical concepts. Some researchers discovered that inconducive language usage impedes mathematics learning. This papers reports on the effect of spreadsheet to the language used by a group of 32 pre-university students in defining “limits”. The data revealed that (i) spreadsheet changes learners’ commandment of language in three aspects which are usage of examples, types of expressions, and accuracy of terminology; (ii) spreadsheet does change learner’ choice expression while learning mathematics regardless their academic ability; and (iii) through spreadsheet environment, learners are able to find a suitable and conducive expression to learn mathematics. This study is significant in such a way that it gives insights to education researchers, educators or curriculum-makers about the roles of spreadsheet in language which then influences mathematics learning.